Event-shape studies of strangeness production in √S = 13 TeV proton–proton collisions with ALICE - Nassirpour Adrian (EPJ Web of Conferences, 2023)
The ALICE Collaboration has observed that the ratio of strange to non-strange hadron yields increases strongly with multiplicity in small collision systems at LHC energies. The origin of this effect is still not fully understood. Models need to incorporate final-state interactions to accommodate the new ALICE results, and require new measurements to discriminate between the various phenomenological descriptions. Two different ALICE studies, aiming to further elucidate the underlying mechanisms of strangeness production in high-multiplicity proton–proton (pp) collisions at √S = 13s=13 TeV, are presented in this proceeding. First, the production of η and π0 are studied as a function of multiplicity, combining several analysis techniques, allowing a measurement for the neutral meson production over a vast transverse momentum (pT) range. This is followed by a measurement of π, K, ϕ, and Ξ as a function of the unweighed transverse spherocity SOPT=1SOpT=1, an event-shape observable which allows us to explore particle production in azimuthal topologies dominated by either hard or soft QCD processes. The results are compared to predictions from PYTHIA and EPOS-LHC.